The Sense of Smell ( SoS ) Atlas: Its Creation and First Application to Investigate COVID ‐19 Related Anosmia With a Comprehensive Quantitative MRI Protocol - Gaviraghi, Marta; Lupi, Eleonora; Grosso, Elena; Fusari, Andrea; Baiguera, Mattia; Monteverdi, Anita; Battiston, Marco; Grussu, Francesco; Kanber, Baris; Prados Carrasco, Ferran; Samson, Rebecca S.; Makaronidis, Janine; et al. (Journal of magnetic resonance imaging, 2025)
The loss of smell, that is, anosmia, is a common symptom in COVID‐19, but the brain alterations behind it are still unclear. In this study, researchers developed the Sense of Smell (SoS) atlas, a new tool that included parts of the brain involved in olfaction. They applied the atlas to advanced MRI metrics of participants with persistent smell loss, participants who had recovered, and healthy controls. Results showed signs of neuroinflammation and axonal damage in persistent anosmia, and myelin changes in recovered anosmia. The SoS atlas provides a valuable tool to study smell‐related brain changes in COVID‐19 and other diseases.